An Enantioselective Mukaiyama Aldol Reaction as the Key Step towards the Tetrahydropyran Core of Psymberin via a γ-Butyrolactone Intermediate - Bielitza, Max; Pietruszka, Jörg (Synlett, 2012)
We report an alternative synthetic route towards the tetrahydropyran core of psymberin. The key steps are a catalytic enantioselective Mukaiyama aldol reaction and a syn reduction, which allowed for the rapid assembly of a γ-lactone as a precursor for the central fragment of the natural product.
Keywords: aldol reaction; asymmetric catalysis; antitumor agent; lactone; enantioselectivity